Traumatic small bowel injury : a diagnosis challenge - Mohamed Saleem SAK; Ismail Mohd Saiboon (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Traumatic small bowel injury is rare complication following a blunt abdominaltrauma. We encountered a case of small bowel injury following a motor vehicle accident that was initially missed during the first presentation due to unremarkable findings in examination. Patient re-presented five days later with bowel ischaemia and was managed accordingly. It is a challenge in diagnosing the injury due to its vague presentation. The usage of Focused Assessment with Sonography for Trauma (FAST) scan as a screening tool in Emergency Department to pick up intra-abdominal injury do have limitations especially in diagnosing small bowel perforation post blunt abdominal trauma. The early phase of small bowel injury post blunt abdominal trauma rarely produces significant free fluid during the FAST scan. It is paramount for the emergency doctors to have a high level of suspicion in high risk cases to provide early supportive treatment and early referral to surgical team. If left undiagnosed bowel ischaemia may lead to catastrophic complication affecting the patient’s morbidity and mortality. In conclusion, each case should be managed and risk stratify individually. Computed tomography abdomen is found to be more superior in detecting bowel injuries, hence, and investigation of choice compared to bedside ultrasonograpy in cases with high level of suspicaion.